2018
DOI: 10.1016/j.ebiom.2018.05.021
|View full text |Cite
|
Sign up to set email alerts
|

By Targeting Atg7 MicroRNA-143 Mediates Oxidative Stress-Induced Autophagy of c-Kit+ Mouse Cardiac Progenitor Cells

Abstract: Therapeutic efficiency of cardiac progenitor cells (CPCs) transplantation is limited by its low survival and retention in infarcted myocardium. Autophagy plays a critical role in regulating cell death and apoptosis, but the role of microRNAs (miRNAs) in oxidative stress-induced autophagy of CPCs remains unclear. This study aimed to explore if miRNAs mediate autophagy of c-kit+ CPCs. We found that the silencing of miR-143 promoted the autophagy of c-kit+ CPCs in response to H2O2, and the protective effect of mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 26 publications
(29 reference statements)
3
17
0
Order By: Relevance
“…Acting as the only E1-like enzyme, Atg7 is located in the hub of the LC3 and Atg12 ubiquitin-like systems and is essential for the expansion of autophagosomal membranes [22]. Accumulating evidence suggests that Atg7 is not only a crucial marker of autophagy, but also participates in the regulation of cell death and survival [32,33], including in cardiac progenitor cells [34]. Previously, we noted that the expression of miR-27a-5p decreased in acute hypoxia-exposed H9c2 cells using a small RNA-seq, as a known hypoxamiR, however, its underlying function in the cardiomyocyte hypoxic response is unclear [13].…”
Section: Discussionmentioning
confidence: 99%
“…Acting as the only E1-like enzyme, Atg7 is located in the hub of the LC3 and Atg12 ubiquitin-like systems and is essential for the expansion of autophagosomal membranes [22]. Accumulating evidence suggests that Atg7 is not only a crucial marker of autophagy, but also participates in the regulation of cell death and survival [32,33], including in cardiac progenitor cells [34]. Previously, we noted that the expression of miR-27a-5p decreased in acute hypoxia-exposed H9c2 cells using a small RNA-seq, as a known hypoxamiR, however, its underlying function in the cardiomyocyte hypoxic response is unclear [13].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, they found that the silencing of miR-143 upregulates Atg7 expression and promotes the autophagy of c-kit + cardiac progenitor cells (CPCs) exposed to H 2 O 2 . 34 Moreover, the transplantation of c-kit + CPCs with miR-143 inhibitor improves cell survival and enhanced therapeutic efficiency in MI. 34 …”
Section: Main Textmentioning
confidence: 99%
“… 34 Moreover, the transplantation of c-kit + CPCs with miR-143 inhibitor improves cell survival and enhanced therapeutic efficiency in MI. 34 …”
Section: Main Textmentioning
confidence: 99%
“…Previous studies have observed autophagy activation in ectopic endometrium of patients with ovarian endometriosis ( 17 , 25 , 26 ). Based on the finding that miR-143-3p displays the potential to regulate autophagy in other diseases ( 27 , 28 ), the present study investigated whether miR-143-3p inhibited ESC proliferation and invasion via inactivating autophagy. The activation of autophagy was analyzed using an autophagy detection kit and western blotting.…”
Section: Resultsmentioning
confidence: 99%